A low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy and its preparation method

CN122669280APending Publication Date: 2026-09-01HENAN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611032648.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-09-01

AI Technical Summary

Technical Problem

[0007]针对现有Ni-Co-Cr-Al系共晶高熵合金Co含量较高、原材料成本较高以及耐空蚀领域应用研究不足的问题,本发明的目的在于提供一种低Co含量耐空蚀Ni-Co-Cr-Al共晶高熵合金及其制备方法

Benefits of technology

本发明提供了一种低Co含量Ni-Co-Cr-Al共晶高熵合金。与传统高钴基耐空蚀合金(如Stellite系列)相比,本发明显著降低了Co使用量及原材料成本;与现有Ni-Co-Cr-Al系共晶高熵合金(Co含量通常不低于10 at.%)相比,本发明通过优化Ni、Cr及Al元素含量,在Co含量为6 at.%至低于10 at.%的条件下仍能够形成稳定的FCC/B2共晶层片组织,实现了该体系共晶高熵合金的低Co化设计,并保持了优异的耐空蚀性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122669280A_ABST
    Figure CN122669280A_ABST
Patent Text Reader

Abstract

This invention discloses a low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy and its preparation method. The alloy composition formula is as follows: Ni a Co b Cr c Al d The alloy contains elements in the following proportions: 48≤a≤54, 6≤b<10, 18≤c≤22, 17≤d≤20, and a+b+c+d=100, all representing atomic percentages. Even with a Co content below 10 at.%, the alloy retains a eutectic lamellar structure composed of FCC and B2 phases, exhibiting excellent cavitation erosion resistance and good abrasion resistance. Under the same cavitation erosion conditions, its mass loss after 20 hours of cavitation erosion is no more than one-tenth that of ZG06Cr16Ni5Mo stainless steel, and superior to Stellite 6 alloy. The alloy is prepared using vacuum arc melting or vacuum induction melting, followed by casting after multiple turns during melting. This alloy is suitable for fluid machinery components such as turbines, pumps, valves, and ship propulsion systems, as well as for cavitation erosion resistant coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metallic materials, specifically relating to a low-Co-content cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy and its preparation method. Background Technology

[0002] Cavitation erosion is a phenomenon where localized high-frequency impact loads are generated during the formation, growth, and collapse of cavitation bubbles in a liquid, leading to plastic deformation, microcrack initiation, and material spalling on the material surface. It is widely observed in fluid machinery such as water turbines, ship propellers, pumps, valves, and aero-engine systems. The microjets and shock waves generated during cavitation erosion can apply instantaneous impact stresses of up to several gigapascals to the material surface in a very short time, severely affecting the service life and operational reliability of flow-through components. Therefore, developing metallic materials with excellent cavitation resistance is of great significance for hydraulic machinery and marine engineering equipment.

[0003] Currently, commonly used cavitation-resistant materials mainly include stainless steel, nickel-based superalloys, cobalt-based alloys, and titanium alloys. Among them, low-carbon martensitic stainless steel, represented by ZG06Cr16Ni5Mo, is widely used in turbine flow components due to its good comprehensive mechanical properties and corrosion resistance. However, this type of material is still prone to severe plastic deformation and surface spalling in long-term cavitation environments, and its cavitation resistance is no longer sufficient to meet the development requirements of high-parameter hydraulic equipment. Although cobalt-based alloys, represented by the Stellite series, have excellent cavitation resistance, their extremely high Co content (usually exceeding 50% by mass) results in high material cost and high density, limiting their large-scale application.

[0004] In recent years, high-entropy alloys have shown great application potential in cavitation erosion resistance due to their high strength, high hardness, excellent corrosion resistance, and good microstructural stability. In particular, Ni-Co-Cr-Al eutectic high-entropy alloys, with their as-cast microstructure consisting of FCC and B2 phases forming a eutectic lamellar structure, possess both high strength and good plasticity, attracting widespread attention in the field of high-temperature structural materials. Studies have shown that the eutectic lamellar structure can effectively coordinate deformation and suppress crack propagation, which is beneficial for improving the service stability of materials under complex loading conditions.

[0005] However, existing Ni-Co-Cr-Al eutectic high-entropy alloys are typically designed with high Co content, with most reported alloys containing no less than 10 at.%. While Co helps improve microstructure stability and mechanical properties, its high price and relatively limited resources significantly increase material costs. In this system, reducing the Co content can easily lead to decreased FCC phase stability and difficulty in eutectic microstructure formation, even resulting in microstructure coarsening or primary phase precipitation, thus affecting microstructure uniformity and overall performance.

[0006] Furthermore, current research on this system of eutectic high-entropy alloys mainly focuses on microstructure control, tensile properties, and high-temperature performance, while studies on their cavitation damage behavior and cavitation resistance are relatively limited. In particular, there is a lack of technical solutions for maintaining the stability of the eutectic lamellar microstructure and achieving excellent cavitation resistance under conditions of reduced Co content. Therefore, developing a Ni-Co-Cr-Al eutectic high-entropy alloy with low Co content, stable microstructure, and excellent cavitation resistance is of great significance for reducing material costs, expanding the engineering application range of this system of eutectic high-entropy alloys, and promoting their application in hydraulic machinery and marine engineering. Summary of the Invention

[0007] To address the issues of high Co content, high raw material costs, and insufficient research on cavitation erosion resistance in existing Ni-Co-Cr-Al eutectic high-entropy alloys, this invention aims to provide a low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy and its preparation method. This alloy, even with reduced Co content, can still form a stable FCC / B2 eutectic lamellar structure and exhibits excellent cavitation erosion resistance, making it suitable for applications in water turbines, pumps, ship propulsion systems, and other fluid machinery flow components.

[0008] The present invention adopts the following technical solution: This invention provides a low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy material, wherein the high-entropy alloy material is composed of Ni. a Co b Cr c Al d Where a, b, c, and d are the atomic percentages of each element, 48≤a≤54, 6≤b<10, 18≤c≤22, 17≤d≤20, and a+b+c+d=100.

[0009] Existing Ni-Co-Cr-Al eutectic high-entropy alloys typically employ a high Co content design to ensure the stable formation of FCC / B2 eutectic lamellar microstructure. This invention optimizes the Ni, Cr, and Al content, controlling the Co content to within the range of 6 at.% to below 10 at.%, while still achieving a stable FCC / B2 eutectic lamellar microstructure, thus balancing microstructural stability and cavitation erosion resistance.

[0010] The element content ranges of this invention were determined based on a comprehensive consideration of the formation, stability, and cavitation erosion resistance of the FCC / B2 eutectic lamellar structure. When the Ni content is below 48 at.% or above 54 at.%, it may affect the phase ratio and lamellar structure uniformity of the FCC / B2 eutectic structure, thereby affecting the stability and overall material performance. When the Co content is below 6 at.%, it is difficult to obtain a stable and uniform FCC / B2 eutectic lamellar structure, which may affect the cavitation erosion resistance of the material. When the Co content reaches or exceeds 10 at.%, although a eutectic structure can still be formed, the increased Co usage raises the material cost, which is not conducive to achieving the low-Co design objective of this invention. When the Cr content is below 18 at.% or above 22 at.%, it may affect the uniformity of the structure and corrosion resistance. When the Al content is below 17 at.% or above 20 at.%, it may affect the formation of the B2 phase and the stability of the FCC / B2 eutectic structure, thereby affecting the overall material performance.

[0011] In a preferred embodiment, 8 ≤ b < 10.

[0012] In some embodiments, the high-entropy alloy material has a eutectic lamellar structure composed of an FCC phase and a B2 phase.

[0013] In some embodiments, the FCC phase in the high-entropy alloy material is a continuous toughening phase, and the B2 phase is a strengthening phase, with the two phases alternating to form a lamellar structure.

[0014] In some embodiments, the high-entropy alloy material is Ni. 52.5 Co8Cr 21 Al 18.5 or Ni 51.5 Co 9.5 Cr 20.5 Al 18.5 .

[0015] In some embodiments, under the same cavitation erosion conditions, the mass loss of the alloy after 20 h of cavitation erosion is significantly lower than that of ZG06Cr16Ni5Mo stainless steel, approximately less than one-tenth of that of ZG06Cr16Ni5Mo stainless steel, and superior to that of Stellite 6 alloy.

[0016] The present invention also provides a method for preparing the above-mentioned low-Co-content cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy, comprising the following steps: 1) Raw material preparation: After converting the atomic percentages to mass percentages according to the set values, weigh out the high-purity Ni, Co, Cr and Al raw materials, and then clean them with alcohol using ultrasonic cleaning and dry them for later use. 2) Alloy smelting: High-purity Al, high-purity Cr, high-purity Co, and high-purity Ni raw materials are sequentially placed into the smelting furnace, and a vacuum of 3×10⁻⁶ is drawn. -3 After the Pa is below 1, high-purity argon gas is introduced for protection. During the melting process, the alloy is turned over and melted repeatedly 4 to 6 times to ensure uniform alloy composition. 3) Casting: The molten alloy liquid is poured into a copper mold and cooled to form the alloy, or it is cooled to form the alloy in a crucible to obtain a Ni-Co-Cr-Al eutectic high-entropy alloy with FCC / B2 eutectic lamellar structure.

[0017] In some implementations, the oxide layer on the surface of high-purity Ni and Co raw materials is removed before feeding. High-purity Cr and Al raw materials do not need to be polished. The purity of all raw materials is above 99.9 wt.%.

[0018] In some implementations, in step 2), a vacuum arc melting furnace or a vacuum induction melting furnace is used for melting.

[0019] In some implementations, in step 2), the melting furnace is a non-consumable vacuum arc melting furnace, and the melting is performed using a current of 100~260 A.

[0020] In some implementations, in step 2), the high-purity Al, high-purity Cr, high-purity Co and high-purity Ni raw materials are placed into the melting furnace in the order of high purity Al, high purity Cr, high purity Co and high purity Ni, with Al and Cr at the bottom of the melting furnace to prevent them from burning.

[0021] In some implementations, in step 2), if the number of flips is less than 4, the elements may not mix sufficiently, affecting the uniformity of the composition; if the number of flips exceeds 6, the improvement on the uniformity of the composition is limited, while the melting time will increase and may lead to an increase in the burning loss of low-melting-point Al.

[0022] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a low-Co-content Ni-Co-Cr-Al eutectic high-entropy alloy. Compared with traditional high-cobalt-based cavitation-resistant alloys (such as the Stellite series), this invention significantly reduces the amount of Co used and the cost of raw materials. Compared with existing Ni-Co-Cr-Al eutectic high-entropy alloys (with a Co content typically not less than 10 at.%), this invention, by optimizing the content of Ni, Cr, and Al elements, can still form a stable FCC / B2 eutectic lamellar structure under conditions where the Co content is 6 at.% to less than 10 at.%, achieving a low-Co design for this system of eutectic high-entropy alloys while maintaining excellent cavitation resistance.

[0023] Under the same cavitation erosion test conditions, the cavitation erosion weight loss of the alloy described in this invention is significantly lower than that of ZG06Cr16Ni5Mo stainless steel and superior to that of Stellite 6 alloy. Specifically, the mass loss after 20 hours of cavitation erosion is less than one-tenth that of ZG06Cr16Ni5Mo stainless steel, demonstrating excellent cavitation erosion resistance.

[0024] Under the same abrasion test conditions, the mass loss of the alloy described in this invention is reduced by more than 30% compared with ZG06Cr16Ni5Mo stainless steel, demonstrating good abrasion resistance.

[0025] The FCC toughening phase and the B2 strengthening phase described in this invention form a synergistic deformation mechanism. The FCC phase can absorb the local plastic deformation energy generated during cavitation impact, while the B2 phase provides higher hardness and resistance to deformation. The synergistic effect of the two phases helps to inhibit crack initiation and propagation, thereby improving the cavitation erosion resistance of the material.

[0026] This invention achieves a uniform eutectic high-entropy alloy using vacuum melting and casting, resulting in a simple preparation process. Although the melting and casting processes used are similar to existing technologies, this invention optimizes the content of Ni, Cr, and Al elements, achieving stable formation of FCC / B2 eutectic lamellar structure under conventional casting conditions with a Co content below 10 at.%, demonstrating promising engineering application prospects. Attached Figure Description

[0027] Figure 1 These are the X-ray diffraction patterns of the cavitation-resistant high-entropy alloys prepared in Examples 1-2 of this invention.

[0028] Figure 2 This is a microstructure of the cavitation-resistant high-entropy alloy prepared in Example 1 of the present invention.

[0029] Figure 3 This is a microstructure diagram of the cavitation-resistant high-entropy alloy prepared in Example 2 of the present invention.

[0030] Figure 4 These are comparative images of the surface morphology of the high-entropy alloy prepared in Example 1 of this invention and ZG06Cr16Ni5Mo stainless steel after cavitation erosion. Among them, (a) is ZG06Cr16Ni5Mo stainless steel and (b) is the high-entropy alloy prepared in Example 1.

[0031] Figure 5 These are comparative images of the surface morphology of the high-entropy alloy prepared in Example 2 of this invention and ZG06Cr16Ni5Mo stainless steel after cavitation erosion. Among them, (a) is ZG06Cr16Ni5Mo stainless steel and (b) is the high-entropy alloy prepared in Example 2. Detailed Implementation

[0032] To facilitate understanding of the present invention, the present invention will be further described below with reference to specific embodiments and accompanying drawings, but the scope of protection of the present invention is not limited to the following embodiments.

[0033] Example 1 A low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy, with the following composition expression (atomic percentage): Ni 52.5 Co8Cr 21 Al 18.5 .

[0034] 1) Raw material preparation: Remove the oxide layer on the surface of high-purity Ni and Co raw materials. High-purity Cr and Al raw materials do not need to be polished. Weigh the raw materials after converting the atomic percentage to the mass percentage according to the set atomic percentage, and then clean them with alcohol ultrasonically and dry them for later use.

[0035] 2) Alloy smelting: Raw materials are placed into a non-consumable vacuum arc melting furnace according to their melting point from low to high, and a vacuum of 3×10⁻⁶ is drawn. -3 After the pressure drops below Pa, high-purity argon gas is introduced for protection, and melting is carried out using a current of 100~260 A. During the melting process, the mixture is turned over and the melting is repeated 6 times, while electromagnetic stirring is performed simultaneously to ensure uniform alloy composition.

[0036] 3) Casting: The molten alloy liquid is cooled and formed in a copper mold under argon protection to obtain a Ni-Co-Cr-Al eutectic high-entropy alloy with FCC / B2 eutectic lamellar structure.

[0037] Analysis of experimental results: The Ni prepared in this embodiment 52.5 Co8Cr 21 Al 18.5 X-ray diffraction patterns of as-cast high-entropy alloys are as follows: Figure 1 As shown, the alloy consists of the FCC phase and the B2 phase. Its microstructure is as follows: Figure 2 As shown, it exhibits a typical eutectic lamellar structure, in which the continuous bright white phase is the FCC toughening phase, enriched with Ni, Co and Cr elements, and the dark phase is the B2 strengthening phase, enriched with Ni and Al elements. The two phases are alternately distributed to form a lamellar structure.

[0038] To comprehensively evaluate the cavitation erosion resistance of the alloy of this invention, the following materials were selected for comparison: (1) ZG06Cr16Ni5Mo stainless steel: a commonly used commercial material for turbine flow parts, used as a benchmark for comparison; (2) Stellite 6 alloy (Co-28Cr-4W-1.1C): a traditional high-Co cavitation resistant alloy, compared as a high-performance commercial alloy.

[0039] The cavitation performance was tested using an ultrasonic cavitation tester with an ultrasonic power of 20 kHz, a wavelength of 50 μm, and deionized water as the medium.

[0040] After cavitation erosion in deionized water for 20 h, the alloy prepared in this example only showed minor spalling and cavitation pits at grain boundaries and phase boundaries, indicating relatively mild cavitation damage (see...). Figure 4 (b) The mass loss was approximately 0.33 mg, while under the same conditions, significant peeling occurred on the surface of ZG06Cr16Ni5Mo stainless steel (see [reference]). Figure 4 (a) shows a mass loss of approximately 5.10 mg. Furthermore, under the same conditions, the Stellite 6 alloy (prepared using the same process) exhibits a mass loss of approximately 0.43 mg. The cavitation erosion resistance of the alloy in this embodiment is approximately 15 times that of ZG06Cr16Ni5Mo stainless steel and superior to that of Stellite 6 alloy.

[0041] The abrasion performance test was conducted in an SQC-200 three-phase flow abrasion test system. 13 kg of quartz sand with a diameter of 1–2 mm and 20 kg of deionized water were added to the test chamber. During the test, the stirring blades were rotated at 1200 r / min to ensure uniform distribution of the sand and gravel and prevent it from settling to the bottom. The abrasion time was 3 hours.

[0042] After 3 hours of abrasion testing under the same conditions, the mass loss of the alloy in this embodiment was approximately 381.68 mg, the mass loss of ZG06Cr16Ni5Mo stainless steel was approximately 624.15 mg, and the mass loss of Stellite 6 alloy was approximately 532.48 mg, indicating that the alloy in this embodiment also has good abrasion resistance.

[0043] Example 2 A low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy, with the following composition expression (atomic percentage): Ni 51.5 Co 9.5 Cr 20.5 Al 18.5 .

[0044] 1) Raw material preparation: Remove the oxide layer on the surface of high-purity Ni and Co raw materials. High-purity Cr and Al raw materials do not need to be polished. Weigh the raw materials after converting the atomic percentage to the mass percentage according to the set atomic percentage, and then clean them with alcohol ultrasonically and dry them for later use.

[0045] 2) Alloy smelting: Raw materials are placed into a non-consumable vacuum arc melting furnace according to their melting point from low to high, and a vacuum of 3×10⁻⁶ is drawn. -3 After the pressure drops below Pa, high-purity argon gas is introduced for protection, and melting is carried out using a current of 100~260 A. During the melting process, the mixture is turned over and the melting is repeated 6 times, while electromagnetic stirring is performed simultaneously to ensure uniform alloy composition.

[0046] 3) Casting: The molten alloy liquid is cooled and formed in a copper mold under argon protection to obtain a Ni-Co-Cr-Al eutectic high-entropy alloy with FCC / B2 eutectic lamellar structure.

[0047] Analysis of experimental results: The Ni prepared in this embodiment 51.5 Co 9.5 Cr 20.5 Al 18.5 X-ray diffraction patterns of as-cast high-entropy alloys are as follows: Figure 1 As shown, the alloy consists of the FCC phase and the B2 phase. Its microstructure is as follows: Figure 3 As shown, it also exhibits a typical eutectic lamellar structure.

[0048] Cavitation erosion performance and abrasion performance were tested under the same conditions as in Example 1.

[0049] After cavitation in deionized water for 20 hours, the alloy in this embodiment only showed minor spalling and cavitation pits at grain boundaries and phase boundaries (see...). Figure 5 (b) The mass loss is approximately 0.37 mg, which is significantly better than that of ZG06Cr16Ni5Mo stainless steel (mass loss is approximately 5.10 mg). Figure 5 (a) and superior to Stellite 6 alloy (mass loss of approximately 0.43 mg). The cavitation erosion resistance of the alloy in this embodiment is approximately 14 times that of ZG06Cr16Ni5Mo stainless steel.

[0050] After 3 hours of abrasion under the same conditions, the weight loss of the alloy in this embodiment was 435.77 mg, the mass loss of ZG06Cr16Ni5Mo stainless steel was approximately 624.15 mg, and the mass loss of Stellite 6 alloy was approximately 532.48 mg.

Claims

1. A low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy material, wherein the high-entropy alloy material is composed of Ni a Co b Cr c Al d ,in, a, b, c, and d are the atomic percentages of each element, 48 ≤ a ≤ 54, 6 ≤ b < 10, 18 ≤ c ≤ 22, 17 ≤ d ≤ 20, and a + b + c + d = 100.

2. The low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy material according to claim 1, characterized in that, The alloy is mainly composed of FCC phase and B2 phase, forming a eutectic lamellar structure.

3. The low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy material according to claim 2, characterized in that, The FCC phase is a continuous toughening phase, and the B2 phase is a strengthening phase. The two phases are alternately distributed to form a lamellar structure.

4. The low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy material according to any one of claims 1 to 3, characterized in that, 8≤b<10。 5. The low-Co-content, cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy material according to any one of claims 1 to 3, characterized in that, The high-entropy alloy material is Ni 52.5 Co8Cr 21 Al 18.5 or Ni 51.5 Co 9.5 Cr 20.5 Al 18.5 .

6. The preparation method of the low-Co-content cavitation-resistant Ni-Co-Cr-Al eutectic high-entropy alloy material according to any one of claims 1 to 5, comprising the following steps: 1) Raw material preparation: Weigh high-purity Ni, high-purity Co, high-purity Cr and high-purity Al according to the set atomic percentage, and clean them with alcohol ultrasonically and then dry them for later use. 2) Alloy smelting: High-purity Al, high-purity Cr, high-purity Co, and high-purity Ni raw materials are sequentially placed into the smelting furnace, and a vacuum of 3×10⁻⁶ is drawn. -3 After the Pa is below 1, high-purity argon gas is introduced for protection. During the melting process, the alloy is turned over and melted repeatedly 4 to 6 times to ensure uniform alloy composition. 3) Casting: The molten alloy liquid is poured into a copper mold and cooled to form the alloy, or it is cooled to form the alloy in a crucible to obtain a Ni-Co-Cr-Al eutectic high-entropy alloy material with FCC / B2 eutectic lamellar structure.

7. The preparation method according to claim 6, characterized in that, Before feeding, the oxide layer on the surface of high-purity Ni and Co raw materials is removed. High-purity Cr and Al raw materials do not need to be polished. The purity of all raw materials is above 99.9 wt.%.

8. The preparation method according to claim 6, characterized in that, In step 2), a vacuum arc melting furnace or a vacuum induction melting furnace is used for melting.

9. The preparation method according to claim 6, characterized in that, In step 2), the melting furnace is a non-consumable vacuum arc melting furnace, and a current of 100~260 A is used for melting.